(untitled) (Global Journal of Human-Social Science, 2022)
The article attempts to characterize the unemployed belonging to the post-war baby boom generation referred to as Baby-boomers born before 1965 Their problems of professional activation on the contemporary dynamically changing labor market were presented It turns out that despite of a significant reduction in the problem of unemployment on the domestic labor market not all age groups of the unemployed are the beneficiaries of these favorable changes What s more the statistics clearly indicate a deterioration of the situation of people over 55 on the labor market In recent years their share in the unemployment structure has increased threefold The phenomenon of the Baby-boomers generation is not only described in the literature but it is also object of scientific reflection However this problem is virtually unnoticeable in the public discourse Rapid changes taking place in the internal and external environment of modern organizations automation robotization Internet development are factors making the eldest unemployed reintegration into the labor market even more difficult These changes may affect professional marginalization but also the progressive social exclusion of people in retirement age